Fuzzy Stability of a General Quadratic Functional Equation. (11th September 2011) - Jin, Sun Sook; Lee, Yang-Hi
Abstract : We investigate a fuzzy version of stability for the functional equationf ( x + y + z ) + f ( x − y ) + f ( x − z ) − f ( x − y − z ) − f ( x + y ) − f ( x + z ) = 0 in the sense of M. Mirmostafaee and M. S. Moslehian.